Atorvastatin Reduces the Incidence of Postoperative Atrial Fibrillation in Statin-Naive Patients Undergoing Isolated Heart Valve Surgery: A Double-Blind, Placebo-Controlled Randomized Trial. (September 2015) - Dehghani, Mohammad Reza; Kasianzadeh, Majid; Rezaei, Yousef; Sepehrvand, Nariman
Background: Atorvastatin has been demonstrated to reduce the incidence of postoperative atrial fibrillation (POAF) in patients undergoing cardiac surgery, but its effect on isolated heart valve surgery is unknown. Methods: In a randomized, double-blinded, placebo-controlled trial, 58 patients who underwent isolated heart valve surgery supported by on-pump cardiopulmonary bypass were randomly assigned to receive either placebo (n = 29) or 40 mg of atorvastatin once daily starting 3 days preoperatively and continuing within 5 days postoperatively (n = 29). A continuous monitoring tool and an electrocardiographic Holter monitoring were used for detecting the POAF (Clinical Trial Registration:www.clinicaltrials.gov ; Unique Identifier: NTC02084069). Results: The patients' median age was 49 years, and 67% were female. In all, 6 (21%) and 13 (45%) cases of POAF were observed in the atorvastatin and placebo groups, respectively ( P = .050). The duration of AF before re-establishment of sinus rhythm was significantly lower in the atorvastatin group than in the placebo group (median of 70 vs 132 minutes, P = .026). The lengths of intensive care unit and hospital stay were comparable between the groups. The increase in postoperative white blood cell count was significantly lower in the atorvastatin group than in the placebo group (median of 1.5 vs 2.3 × 10 3 /µL, respectively, P = .019). After adjustment, the atorvastatin treatment was associated with a decrease in the risk of developing POAF (odds ratio 0.122, 95% confidence interval 0.027-0.548, P = .006). Conclusion: Perioperative treatment with 40 mg of atorvastatin is useful to decrease the incidence of POAF in the statin-naive patients undergoing isolated heart valve surgery.